SCRUM Metode Implementation for Build Up Responsive Shoes Laundry Front Web End - Simanjuntak, Iskandar Zulkarnain; Tembusai, Zoelkarnain Rinanda (Journal of Technology and Computer, 2024)
This research examines the development of a responsive website front end for shoe laundry services using the SCRUM method. In the context of the development of information technology, especially the internet, web-based websites are important for human life, but there are still some people who do not understand the development process. This research aims to introduce and implement the principles of responsive website design, as well as facilitate understanding and skills in website development to shoe laundry businesses. The SCRUM method was chosen to ensure website development in accordance with user needs and rapid market dynamics. The results include the development of a responsive and user-friendly front end website using HTML, CSS, JavaScript, and ReactJS. This project provides benefits to the campus as an example of the application of technology in the industrial world and increases the researcher's knowledge in web development and the SCRUM method.